Pengembangan Perangkat Pembelajaran Model Discovery Learning pada Materi Elastisitas dan Hukum Hooke untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Harmaen Agustina Kasanova; Hairunnisyah Sahidu; Susilawati Susilawati (Department of Physics Education, Universitas Mataram, 2022)
This research aims to develop a discovery learning model of learning device on elasticity and hooke’s law to improve students’ physics learning outcomes that are valid, practical, anf effective. Learning device were developed in forms of a syllabus,Lesson Plan, Student Worksheet, evaluasi tools. This type of research is research and development (R&D) with a procedural development model, named the 4D model (define, design, develop, and disseminate). The average percentage of learning device validation related to syllabus, Lesson Plan, Student Worksheet, evaluasi tools achievement were 86.50%, 83.00%, 82.00%, and 86.50%. The practicality of learning device was able to see from the percentage of the practicality of learning device questionnaires by student that is 94,55%. For the effectiveness of learning devices was proved from the increasing of students' cognitive learning achievement that calculated by the N-Gain equation, the results was obtained 0.70 for the hight category. Based on these results, the learning device that developed valid, practically and effective to use with some of revisions.